AISC LRFD Rules for Block Shear in Bolted Connections—A Review - Kulak, Goeffrey L.; Grondin, G.Y. (Engineering Journal, 2001)
The AISC LRFD specification (LRFD, 1999) for the design of steel structures contains provisions for what is customarily termed block shear. Notionally, this refers to the displacement of a block of material. It is usually associated with bolted details because a reduced area is present in that case, but in principle it can also be present in welded details. This paper deals only with bolted connections, however. This examination has identified that use of the LRFD Specification rules for block shear leads to conservative designs for gusset plates, non-conservative designs for coped beams, and satisfactory results for angles. Importantly, in most cases these rules do not reflect the mode of failure observed in the tests.